The effectiveness of used plastic bottles as media in the biofilter for reducing MBAS and phosphate in the laundry liquid waste - Syah, Firman; M.Hasbi, M.Hasbi; Purwanto, Eko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractUsed plastic bottles can be used for biofilter media as microorganisme may attach in the bottle surface. To understand the effectiveness of the number of plastic bottles in the anaerob tank in reducing MBAS and phosphate in laundry waste, a research has been done in October-December 2019. This research uses used plasctic bottles with 11 cm height and 6 cm diameter. There were 3 treatments applied, namely P1 (25 bottles) with surface area 11.540 cm2,  P2 (50 bottles) with surface area 23.080 cm2 and  P3 (75 bottles) with surface area 34.619 cm2, 3 replications in each treatments. The seeding time of the biofilm was 25 days. The effectiveness of MBAS decrement was 56.3%, 73.7% dan 80.9% in P1, P2, and P3respectively. While the effectiveness of phospate decrement was 54.9%, 73.3% and 85.0%. in P1, P2, and P3 respectively. Based on data obtained, it can be concluded that the biofilter that was completed with plastic bottleswas able to reduce the MBAS dan phosphate in the laundry liquid waste and P3 provided the best result.Keywords: anaerob, bacteri, waste management, plastic bottle re-use